Sunnite-Shiite Polemics in Norway - Linge, Marius (FLEKS - Scandinavian Journal of Intercultural Theory and Practice, 2016)
As a result of the so-called Islamic State’s expansion in Syria and Iraq, Sunnite-Shiite polarization appears as an increasingly relevant topic, including among Muslims in Europe. Taking into consideration that this is a relatively new manifestation of intolerance in the West, such intra-Islamic tensions remain an under-researched subject and are superficially described as a reproduction of Middle Eastern so-called sectarianism. While this article recognizes the regional origin of exclusivist Islamic narratives and their dissemination by transnational Islamic networks, it also highlights the fact that Sunnite-Shiite polemics are rearticulated in new local contexts. In light of the IS’s anti-Shiism in particular, the public debate in Norway about “Islamic radicalism” is currently being rationalized by many Norwegian Muslims in terms of the “moderate self” versus the “extreme other”, notably across the Sunnite-Shiite divide.